Hadith #2337 - Sunan Abi Dawud - Aabad bin al-Wam bin عباد بن العوام; Sa'd bin Tariq, Abu Malik سعد بن طارق بن أشيم أبو مالك الأشجعي; Sa'id bin Sulaiman al-Dabi سعيد بن سليمان - سعدويه الضبي (Sunan Abi Dawud)
AbdulAziz ibn Muhammad said: Abbad ibn Kathir came to Medina and went to the assembly of al-Ala’. He caught hold of his hand and made him stand and said: O Allah, he narrates a tradition from his father on the authority of AbuHurayrah who reported the Messenger of Allah (ﷺ) as saying: When the middle of Sha’ban comes, do not fast. Al-Ala’ said: O Allah, my father narrated this tradition on the authority of AbuHurayrah from the Prophet (ﷺ)
Grade: Sahih

Hadith #4507 - Sunan Abi Dawud - Aabad bin al-Wam bin عباد بن العوام; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Da'ud bin Rshyd داود بن رشيد; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Sa'id bin Abi Sa'id; Sa'id bin Sulaiman al-Dabi سعيد بن سليمان - سعدويه الضبي; Sufyan bin Hussain bin al-Hasan سفيان بن حسين السلمي (Sunan Abi Dawud)
The Prophet (ﷺ) said: I will not forgive anyone who kills after accepting blood-wit
Grade: Da'if

Hadith #4538 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Muhammad bin Abi Ghalb محمد بن أبي غالب القومسي; Sa'id bin Sulaiman al-Dabi سعيد بن سليمان - سعدويه الضبي; Sulaiman bin Khatir al-'Abdi سليمان بن كثير العبدي; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
The Prophet (ﷺ) Said: The disputants should refrain from taking retaliation. The one who is nearer should forgive first and then the one who is next to him, even if (the one who forgives) were a woman. Abu Dawud said: I have been informed that forgiving by women in the case of murder is permissible if a woman were one of the heirs (of the slain). I have been told on the authority of Abu ‘Ubaid about the meaning of the word yanhajizu, that is, they should refrain from retaliation.
Grade: Da'if

Hadith #4589 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Sa'id bin Sulaiman al-Dabi سعيد بن سليمان - سعدويه الضبي; Sulaiman bin Khatir al-'Abdi سليمان بن كثير العبدي; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Khalid with a different chain of narrators to the same effect.
Grade: Hasan

Hadith #5258 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Abu Layla; Ali bin Hashim bin al-Burayd علي بن هاشم بن البريد; Muhammad bin 'Abdur Rahman bin Abi Layla محمد بن عبد الرحمن بن أبي ليلى; Sa'id bin Sulaiman al-Dabi سعيد بن سليمان - سعدويه الضبي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
He should give it a warning three times. If it appears to him after that, he should kill it, for it is a devil.
Grade: Sahih